2018
DOI: 10.1007/s12640-018-9890-6
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Is an Independent Predictor of 30-Day Mortality of Intracerebral Hemorrhage Patients: a Validation Cohort Study

Abstract: In a previous study in patients with intracranial hemorrhage (ICH), we found an association between high neutrophil-to-lymphocyte ratio (NLR) with poor short-term mortality. In the current study, this preliminary finding was validated using an independent patient cohort. A total of 181 ICH patients (from January 2016 to December 2017) were included. Diagnosis was confirmed using computed tomography (CT) in all cases. Patient survival (up to 30 days) was compared between subjects with high NLR (above the 7.35 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 47 publications
(57 reference statements)
6
42
0
4
Order By: Relevance
“…In the present study, we found NLR to be associated with poor short-term survival, confirming previous results from our research group [23][24][25] . We found that NIHSS score was an independent risk factor of death, and that it correlated positively with PAUD.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found NLR to be associated with poor short-term survival, confirming previous results from our research group [23][24][25] . We found that NIHSS score was an independent risk factor of death, and that it correlated positively with PAUD.…”
Section: Discussionsupporting
confidence: 93%
“…A high NLR at admission was reported to be an indicator of poor outcome in ICH patients, though the mechanism remained unclear. [11] In the current study, cervical tSCI patients who had a higher NLR were more likely to have a poor outcome measured by AIS grade, which is consistent with results from ICH or TBI patients. Moreover, the level of NLR is similar with that in TBI patients, and much higher than the level in ICH patients.…”
Section: Discussionsupporting
confidence: 86%
“…Favorable prognostic value of circulating NLR at admission had been reported in ICH and TBI patients. [11,18] It is expected that the prognostic value of NLR would be favorable in predicting the outcome of patients with cervical tSCI which shares the similar secondary injury mechanism as TBI. Univariate analysis showed signi cant correlation between NLR and patient outcome, the prognostic effect remained substantial following adjusted analysis, suggesting NLR is of considerable prognostic relevance in cervical tSCI patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After focal tSCI, circulating neutrophils can be observed to be recruited to the site of injury within 1 h, which is considered as an indicator of acute inflammation [9]. It was reported that high neutrophils and low lymphocytes level in the peripheral blood at admission were independently associated with poor outcome of intracerebral hemorrhage (ICH) patients, and the neutrophil-to-lymphocyte ratio (NLR) was readily available as an outcome predictor [10,11]. Nevertheless, the prognostic value of NLR for the outcome of tSCI patients has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%